Human Lymphoma: Clinical Implications of the REAL Classification - Mason, David Y.; Harris, Nancy Lee (Springer London, 1999)
Human Lymphoma: The Clinical Implications of the REAL Classification is a unique volume. It is based on the recent developments in classification and overall understanding of human lymphoid neoplasms which are relatively common neoplasms and which epidemiological evidence suggests are increasing in frequency. This field has been the cause of confusion in the past as a result of conficting ideas on the classification of lymphoma and related diseases. However a new vision of the field has emerged and the is encapsulated in the pioneering REAL classification and in a forthcoming WHO scheme, both of which are covered in the book. The volume will appeal to hematologists, pathologists and oncologists and will, thanks to a diverse and expert authorship, serve to increase the working knowledge of all three groups